Penerapan Digital Marketing dan Teknologi Alat Pemintal Benang Tenun Otomatis Ramah Lingkungan pada Pengrajin Lurik Mulyo Cawas Klaten Jawa Tengah - Adhianty Nurjanah; Linda Kusumastuti Wardana; Wahyudi Wahyudi; Riski Apriliani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Dusun Tegalmulyo Cawas Klaten, Central Java, is one of the centers for producing striated weaving using Non-Machine Weaving Equipment (ATBM). ATBM, owned by craftsmen, is a legacy from their predecessors and has been running for decades, including Kreasi's partner and Lurik Weaving Craftsman